2008
DOI: 10.1302/0301-620x.90b4.19648
|View full text |Cite
|
Sign up to set email alerts
|

The five-year results of the Birmingham Hip Resurfacing arthroplasty

Abstract: Few independent studies have reported the outcome of resurfacing arthroplasty of the hip. The aim of this study was to report the five-year clinical outcome and seven-year survival of an independent series. A total of 610 Birmingham Hip Resurfacing arthroplasties were performed in 532 patients with a mean age of 51.8 years (16.5 to 81.6). They were followed for between two and eight years; 107 patients (120 hips) had been followed up for more than five years. Two patients were lost to follow-up. At a minimum o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
114
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(124 citation statements)
references
References 26 publications
(14 reference statements)
9
114
1
Order By: Relevance
“…They have the potential to substantially reduce long-term wear-induced osteolysis as the major cause of failure. Short-term clinical follow-up reports on MoM hip resurfacing have been encouraging (Sieber et al 1999, MacDonald et al 2003, Treacy et al 2005, Hing et al 2007, Steffen et al 2008 with extremely low rates of failure reported in spite of the fact that patients have resumed high-level occupational and leisure activities. Medium-to long-term outcome is, however, unknown.…”
mentioning
confidence: 99%
“…They have the potential to substantially reduce long-term wear-induced osteolysis as the major cause of failure. Short-term clinical follow-up reports on MoM hip resurfacing have been encouraging (Sieber et al 1999, MacDonald et al 2003, Treacy et al 2005, Hing et al 2007, Steffen et al 2008 with extremely low rates of failure reported in spite of the fact that patients have resumed high-level occupational and leisure activities. Medium-to long-term outcome is, however, unknown.…”
mentioning
confidence: 99%
“…Considering the BHR implant, which has performed well clinically since its introduction in 1997, characteristic adaptations include narrowing of the femoral neck, medial trabecular densification and formation of pedestal lines around the metaphyseal stem (McMinn et al 1996;Pollard et al 2006;Hing et al 2007;Steffen et al 2008). Further changes observed after retrieval include resorption inside the femoral head.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, porous-coated press-fit acetabula have demonstrated similar survivorship at a mean followup of 5 to 10 years with their use in hip resurfacing arthroplasty [2,7,9,19,23]. However, underreaming the acetabulum for fixation of an oversized press-fit component has been associated with acetabular fractures [3,10] and incomplete component seating [2,6,12].…”
Section: Introductionmentioning
confidence: 99%